An Ecological Study of the Forest Types in the Lolab Valley and the Adjoining Areas - Inayatullah, Mir; Ticku, B. L. (Indian Forester, 1965)
A precise knowledge of the ecological status of a community in a forest area under scientific management is indispensable to a forester; since silvicultural operations designed to "improve" the crop are fundamentally based on accelerating, retarding or arresting the natural succession of vegetation. With this object in view a complete ecological study has been done in the Lolab Valley and the adjoining ranges (which form an escarpment of the Valley) under the broad classification of the forest type described earlier (lnayatullah and Ticku 1964).